Anti-melanogenic activity of Myristica fragrans extract against Aspergillus fumigatus using phenotypic based screening - Shanu Hoda; Maansi Vermani; Rajesh K. Joshi; Jata Shankar; Pooja Vijayaraghavan (BMC, 2020)
Abstract Background Aspergillus fumigatus, an opportunistic fungal pathogen is associated with a wide array of diseases. It produces 1, 8-dihydroxy naphthalene (DHN) melanin that imparts greenish grey color to conidia and is an important virulence factor. It masks various molecular patterns associated with A. fumigatus and protects the fungus from host immune system. Myristica fragrans, enriched with secondary metabolites has been traditionally used for the treatment of infectious and inflammatory diseases. The present study was aimed to explore the anti-melanogenic effect of M. fragrans extracts on A. fumigatus. Methods M. fragrans extracts (hexane, chloroform, methanol and ethanol) were prepared through polarity guided extraction. Phytochemical analysis was performed to detect the chemical constituents of the extracts. The minimum effective concentration (MEC) of the extracts against A. fumigatus melanin was determined by broth micro-dilution assay. Various virulence factors were assayed by spectrophotometric methods. Electron microscopic studies were performed to evaluate the effect of the hexane extract of M. fragrans on A. fumigatus cell surface morphology. The major active compounds of the extract were detected by gas chromatography-mass spectrometry (GC-MS). Docking was performed to study the interaction between the major identified compounds and the ketosynthase domain of polyketide synthase protein. Results The results indicated that the hexane extract of M. fragrans inhibited melanin production (76.09%), reduced ergosterol content (83.63%) and hydrophobicity of the cell (72.2%) at the MEC of 0.078 mg/mL. Altered conidial surface, disappearance of protrusions and absence of melanin layer on outer cell surface was observed in electron microscopy. Forty-two compounds were identified by GC-MS. The main constituents were identified as sabinene (12.2%), linoleic acid (11.7%), hexadecanoic acid (10.5%), safrole (8.1%) and elemicin (7.8%). Docking studies revealed that hexadecanoic acid, its derivative compound cis-9-hexadecenal and isoeugenol have lower binding energy forming proper hydrogen bond with ketosynthase domain of polyketide synthase protein. Conclusion The study concludes that the extract of M. fragrans has potential antifungal properties that can be explored in combination with available antifungals. This combination approach may be helpful for large number of patients suffering with A. fumigatus infections.